The recombinant Link module of human TSG-6 suppresses cartilage damage in models of osteoarthritis: a potential disease-modifying OA drug - Drummond, SP; Bartnik, E; Kouvatsos, N; Scott, JL; Dyer, DP; Thomson, JM; Price, AJ; Anand, S; Biant, LC; Leeuw, T; Herrmann, M; Milner, CM; et al. (Elsevier, 2023)
Objective To investigate the role of endogenous TSG-6 in human osteoarthritis (OA) and assess the disease-modifying potential of a TSG-6-based biological treatment in cell, explant and animal models of OA. Design Knee articular cartilages from OA patients were analyzed for TSG-6 protein and mRNA expression using immunohistochemistry and RNAscope, respectively. The inhibitory activities of TSG-6 and its isolated Link module (Link_TSG6) on cytokine-induced degradation of OA cartilage explants were compared. Human mesenchymal stem/stromal cell-derived chondrocyte pellet cultures were used to determine the effects of Link_TSG6 and full-length TSG-6 on IL-1α-, IL-1β-, or TNF-stimulated ADAMTS4, ADAMTS5, and MMP13 mRNA expression. Link_TSG6 was administered i.a. to the rat ACLTpMMx model; cartilage damage and tactile allodynia were assessed. Results TSG-6 is predominantly associated with chondrocytes in regions of cartilage damage where high TSG-6 expression aligns with low MMP13, the major collagenase implicated in OA progression. Link_TSG6 is more potent than full-length TSG-6 at inhibiting cytokine-mediated matrix breakdown in human OA cartilage explants;>50% of donor cartilages, from 59 tested, were responsive to Link_TSG6 treatment. Link_TSG6 also displayed more potent effects in 3D pellet cultures, suppressing ADAMTS4, ADAMTS5, and MMP13 gene expression, which was consistent with reduced aggrecanase and collagenase activities in explant cultures. Link_TSG6 treatment reduced touch-evoked pain behavior and dose-dependently inhibited cartilage damage in a rodent model of surgically-induced OA. Conclusions Link_TSG6 has enhanced chondroprotective activity compared to the full-length TSG-6 protein and shows potential as a disease modifying OA drug via its inhibition of aggrecanase and collagenase activity.